Imaging genomics discovery of a new risk variant for Alzheimer's disease in the postsynaptic SHARPIN gene. Issue 13 (18th June 2020) - Soheili‐Nezhad, Sourena; Jahanshad, Neda; Guelfi, Sebastian; Khosrowabadi, Reza; Saykin, Andrew J.; Thompson, Paul M.; Beckmann, Christian F.; Sprooten, Emma; Zarei, Mojtaba; ,
Abstract: Molecular mechanisms underlying Alzheimer's disease (AD) are difficult to investigate, partly because diagnosis lags behind the insidious pathological processes. Therefore, identifying AD neuroimaging markers and their genetic modifiers may help study early mechanisms of neurodegeneration. We aimed to identify brain regions of the highest vulnerability to AD using a data‐driven search in the AD Neuroimaging Initiative (ADNI, n = 1, 100 subjects), and further explored genetic variants affecting this critical brain trait using both ADNI and the younger UK Biobank cohort ( n = 8, 428 subjects). Tensor‐Based Morphometry (TBM) and Independent Component Analysis (ICA) identified the limbic system and its interconnecting white‐matter as the most AD‐vulnerable brain feature. Whole‐genome analysis revealed a common variant in SHARPIN that was associated with this imaging feature (rs34173062, p = 2.1 × 10 −10 ). This genetic association was validated in the UK Biobank, where it was correlated with entorhinal cortical thickness bilaterally ( p = .002 left and p = 8.6 × 10 −4 right), and with parental history of AD ( p = 2.3 × 10 −6 ). Our findings suggest that neuroanatomical variation in the limbic system and AD risk are associated with a novel variant in SHARPIN. The role of this postsynaptic density gene product in β1‐integrin adhesion is in line with the amyloid precursor protein (APP) intracellular signaling pathway and the recent genome‐wide evidence.